2004
DOI: 10.1023/b:jarg.0000031251.57848.04
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Perfusion Essential for Spermatogenesis and Outcome of Testicular Sperm Extraction (TESE) for Assisted Reproduction

Abstract: Purpose : In order to determine if there are areas of major and minor perfusion in a single testicle and if the quality of sperm is correlated with quantity of perfusion we collected testicle tissue for TESE in accordance to the local testicle tissue perfusion. Methods : A patient undergoing TESE underwent testicular perfusion mapping using contrast enhanced ultrasound. The exposed tissue was scanned with a Laser Doppler scanner and perfusion rates were determined measuring tissue perfusion units (TPUs). Tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 28 publications
0
30
0
1
Order By: Relevance
“…Our findings conflict with the results of other groups that found a relationship between blood flow, as measured by ultrasound, and sperm-positive biopsies in small cohorts of patients with NOA. [3][4][5] As we did not use Doppler ultrasound or laser Doppler flowmetry but instead assessed testicular vascularisation through an operative microscope, these conflicting results might be explained by different methodologies. However, our findings concur with the assessment of Ramasamy et al 17 Based on the experience of 900 men who underwent M-TESE for NOA between 2000 and 2010, Ramasamy et al 17 believe that a close correlation does not exist between testicular blood flow and the areas of spermatogenesis in patients with NOA, although this correlation was not specifically studied during their investigations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings conflict with the results of other groups that found a relationship between blood flow, as measured by ultrasound, and sperm-positive biopsies in small cohorts of patients with NOA. [3][4][5] As we did not use Doppler ultrasound or laser Doppler flowmetry but instead assessed testicular vascularisation through an operative microscope, these conflicting results might be explained by different methodologies. However, our findings concur with the assessment of Ramasamy et al 17 Based on the experience of 900 men who underwent M-TESE for NOA between 2000 and 2010, Ramasamy et al 17 believe that a close correlation does not exist between testicular blood flow and the areas of spermatogenesis in patients with NOA, although this correlation was not specifically studied during their investigations.…”
Section: Resultsmentioning
confidence: 99%
“…However, small studies have suggested a correlation between testicular perfusion and focal spermatogenesis. 3,4 In a study of 12 patients with NOA, sperm quality was highest in areas of high tissue perfusion, as determined by Doppler ultrasound and laser Doppler flowmetry. 5 Schlegel observed that sperm-containing regions can be identified microsurgically, as seminiferous tubules that contain many developing germ cells, rather than Sertoli cells alone, are likely to be larger and more opaque than tubules without sperm production.…”
Section: Introductionmentioning
confidence: 99%
“…microdissection TESE) may be required [9][10][11]. In this context, fine-needle aspiration mapping prior to TESE [12] or tissue perfusion-controlled guided biopsies [13] turned out to be useful to locate areas of spermatogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, varicocele is believed to be among the most common correctable etiologies of infertility in men [9]. Vascular perfusion appears to affect the quality of spermatogenesis [30]. Indeed, several reports have shown associated derangements in semen parameters when varicocele is present [11,12], and shown improvements when varicocele is corrected [8,10,14,15,22,31,32].…”
Section: Repaired Not Repairedmentioning
confidence: 99%